Uso de sombras na correção do efeito vinhete - Imai, Nilton Nobuhiro [UNESP]; Polidório, Airton Marco; Tommaselli, Antonio Maria Garcia [UNESP]; Barros, Anderson De Freitas [UNESP] (Universidade Federal do Paraná, 2014)
When registering spectral radiance from surface targets, digital numbers recorded by the imagery sensor may vary. Such variation causes imperfections on the images coming from aerial surveys. Variation in the image brightness related to the distance from the center of the image is known as the vignetting effect. Correcting this effect aims at achieving an homogeneous image brightness. The purpose of this paper is to present a specific methodology to determine a model in order to minimize this vignette effect based on a model fit by Least Squares Method (LSM), using digital numbers (DN) from shadowed regions. The main hypothesis is that the recorded DN of shadow pixels should be suitable to model the vignetting effect. Considering that the vignetting effect could be modeled as a trend of spatial image variation, a trend surface analysis of a sample of pixels from shadowed regions was carried out. Two approaches were adopted to represent the shadow regions of an image. The first one takes into account the components R, G, B of the aerial image within the visible spectral band, and the second one considers the component I of the HSI image. In order to evaluate the methodology, a study case with a color aerial image was carried out. The findings showed that the best results were obtained by applying the model in the RGB components, which allows to conclude that the vignetting effect can be modeled based on trend surfaces fit on shadow regions DN.

Variações do valor de brilho de alvos da superfície podem ocorrer no registro realizado por sensores imageadores. A variação desses valores de brilho que ocorrem em função da distância do pixel ao centro da imagem é conhecida como efeito vinhete e sua correção tem como objetivo oferecer um ajuste de brilho homogêneo na imagem. A proposta deste trabalho é apresentar uma metodologia para determinar um modelo de minimização desse efeito vinhete com base numa função ajustada pelo método dos mínimos quadrados, a partir dos valores de brilho de sombras. Uma das hipóteses adotadas é de que as variações de brilho registrados em pixels de sombra sejam adequadas para representar os efeitos do vinhete. Considerando que o efeito vinhete possa ser modelado como uma tendência de variação espacial dos valores de brilho da imagem foi realizada a análise de superfície de tendência de um conjunto de pixels amostrados em regiões de sombras. Foram adotadas duas abordagens para representar os valores de sombras que foram processados. A primeira, baseada nos componentes R, G e B da imagem colorida; e a segunda estratégia, do componente I da imagem HSI. A fim de avaliar a metodologia realizou-se um estudo de caso com uma imagem aérea colorida. Os experimentos mostraram que o melhor resultado foi obtido pela aplicação do modelo nas componentes RGB, permitindo concluir que o efeito vinhete pode ser modelado com base em superfícies de tendência ajustadas aos valores RGB das sombras.
Using shadows to correct vignetting effects
Keywords: Sensoriamento Remoto; Efeito Vinhete; Análise de Variância; Superfície de Tendência; Remote Sensing; Vignetting Effect; Analysis of Variance; Trend Surface